Construction of a binary S-scheme S-g-C3N4/Co-ZF heterojunction with enhanced spatial charge separation for sunlight-driven photocatalytic performance. Issue 36 (16th August 2022) - Bahadur, Ali; Iqbal, Shahid; Javed, Mohsin; Hassan, Syeda Saba; Nadeem, Sohail; Akbar, Ali; Alzhrani, Rami M.; Al-Anazy, Murefah Mana; Elkaeed, Eslam B.; Awwad, Nasser S.; Ibrahium, Hala A.; Mohyuddin, Ayesha
Abstract : A novel S-scheme photocatalyst system is constructed utilizing the hydrothermal technique and S-g-C3 N4 /Co-ZF binary material. Abstract : A step-scheme (S-scheme) photocatalyst made of sulfurized graphitic carbon nitride/cobalt doped zinc ferrite (S-g-C3 N4 /Co-ZF) was constructed using a hydrothermal process because the building of S-scheme systems might increase the lifespan of highly reactive charge carriers. Utilizing cutting-edge methods, the hybrid photocatalyst was evaluated by employing TEM, XPS, XRD, BET, FTIR, transient photo-response, UV-vis, EIS and ESR signals. In order to create a variety of binary nanocomposites (NCs), nanoparticles (NPs) of 6% cobalt doped zinc ferrite (Co-ZF) were mixed with S-g-C3 N4 at various concentrations, ranging from 10 to 80 wt%. For photocatalytic dye removal, a particular binary NC constructed between S-g-C3 N4 and Co-ZF produces a huge amount of catalytic active sites. The findings showed that loading of S-g-C3 N4 on 6% Co-ZF NPs serves as a good heterointerface for e − /h + separation and transportation through the S-scheme S-g-C3 N4 /Co-ZF heterojunction. By boosting the hybrid system's BET surface area for the photocatalytic process, the addition of 6% Co-ZF improves the system's ability to absorb more sunlight and boosts its photocatalytic activity. The highest photo-removal effectiveness (98%), which is around 2.45 times higher than that of its competitors, was achieved by the hybrid photocatalyst system with an ideal loading of 48% Co-ZF. Furthermore, the trapping studies showed that the primary species involved in the MB aqueous photo-degradation were ˙OH − and h + .